Universal Basic Income - Rey Pérez, José Luis (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The present paper analyzes the proposal of the universal basic income starting from its origins until the debate that takes place at present, where the question does not focus so much on the normative foundation of it, as on its political and economic viability. In addition, the differences with the minimum incomes or the minimum vital income that was approved by the Spanish Government in June 2020 are analyzed. Finally, it is proposed that universal basic income may play a relevant role in the current context of labor relations characterized by their precariousness, playing as a counterweight to it.
Keywords: universal basic income; minim incomes; minimum vital income; precariousness; right to work